2020
DOI: 10.1021/jacs.0c06820
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Quinone Methides Enabling Rapid, Site-Specific, and Photocontrolled Protein Modification with Amine Reagents

Abstract: Site-specific modification of proteins with functional molecules provides powerful tools for researching and engineering proteins. Here we report a new chemical conjugation method which photocages highly reactive but chemically selective moieties, enabling the use of protein-inert amines for selective protein modification. New amino acids FnbY and FmnbY, bearing photocaged quinone methides (QMs), were genetically incorporated into proteins. Upon light activation, they generated highly reactive QM, which rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Therefore, a labeling method with short linker will enrich the labeling toolbox and may benefit smFRET measurement under certain circumstance. 35 In this work, we demonstrate the highly efficient and specific genetic incorporation of the novel unnatural amino acid, 2-amino-3-(4-hydroselenophenyl) propanoic acid, or seleno-phenylalanine (SeF) (Fig. 2G), through genetic code expansion, followed by Se-Click reaction to conjugate the Bodipy593 fluorophore on proteins (Fig.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, a labeling method with short linker will enrich the labeling toolbox and may benefit smFRET measurement under certain circumstance. 35 In this work, we demonstrate the highly efficient and specific genetic incorporation of the novel unnatural amino acid, 2-amino-3-(4-hydroselenophenyl) propanoic acid, or seleno-phenylalanine (SeF) (Fig. 2G), through genetic code expansion, followed by Se-Click reaction to conjugate the Bodipy593 fluorophore on proteins (Fig.…”
Section: Introductionmentioning
confidence: 88%
“…Through GST dimeric cross‐linking, nine amino acid residues with nucleophilic side chains (Cys, Lys, His, Tyr, Trp, Met, Arg, Asn, and Gln) in close proximity were found to covalently linked with the photoactivated FnbY 26 and FmnbY (unpublished results). What is more, when there is no nucleophilic residue nearby, the photoactivated FnbY and FmnbY in proteins also allow rapid (<10 s) conjugation of amine or thiol reagents 27 …”
Section: Covalently Targeting Various Amino Acid Residuesmentioning
confidence: 99%
“…We demonstrated that fluoroacetamide, installed on Uaa FAcK (Figure 2a) and previously thought inert in cells, actually reacted with the thiol group of cysteine when in proximity. Introducing the functional group into testing proteins as a Uaa cannot always be successful, so a facile method to attach functionalities onto proteins is later developed 27 . Uaa FnbY and FmnbY are genetically incorporated into proteins at the desired site, which generate QM upon UV activation (Figure 2d).…”
Section: Covalent Bonding Between Two Proteinsmentioning
confidence: 99%
“…MaPylRS is also more stable and has higher expression level in E. coli cells [28] . Transplantation of mutations identified in the active sites of MmPylRS or MbPylRS into the MaPylRS often lead to improved ncAA incorporation efficiency in E. coli [29,30] . MaPylRS protein can also be concentrated several fold higher without aggregation in vitro , which greatly facilitates cell‐free genetic code expansion as well [28] …”
Section: Figurementioning
confidence: 99%